The Challenges of Women Housed in Internally Displaced Persons (IDP) Camps During an Armed Conflict in Ethiopia. Issue 1 (February 2023) - Desalegn, Shambel; Kasseye, Eyayu; Gebeyaw, Getachew; Meshelemiah, Jacquelyn C.A.
The outbreak of an ethnically and politically motivated armed warfare in Tigray in 2020, spread to the Amhara and Afar regions in Ethiopia, wreaking havoc on civilians. This armed conflict has had a significant impact on the lives of women who have been uprooted from their homes and are now living in internally displaced persons (IDP) camps. The purpose of this study was to examine the challenges faced by women living in two IDP camps in Dabat and Debark, Ethiopia. In-depth interviews were used to gather data from 13 participants. Challenges emerged that relate to three major themes: systemic (gender-based violence, family separation/disintegration, human trafficking, and genocide); psychological (trauma and stress; loss of home/personal belongings); and social (lack of social security and stability, reintegration and resettlement problems, unmet basic needs [physiological and physical health], and maladministration of supplies. The results of the study suggest that internally displaced women in Ethiopia are a group of targeted and victimized civilians suffering from a wide range of atrocities that are rooted in their gender identity, marginalized status, and extreme vulnerability. Lawmakers, politicians, advocacy groups, social work practitioners and women's activists must all advocate for stronger sanctions for those who perpetrate violence against women.